The risk level for individuals to suffering from NCDs based on CERDIK behavior - Suprajitno Suprajitno; Sri Mugianti (International Journal of Public Health Science (IJPHS), 2022)
The use of tobacco, inactivity, alcohol consumption, and an unbalanced diet are factors that cause non-communicable diseases (NCDs) and are considered behavioral factors. Behavior includes knowledge, attitudes, and practice about periodic health checks, getting rid of cigarettes, regular physical activity, a balanced healthy diet, adequate rest, and managing stress (CERDIK) and can be used as a way to measure the risk of an individual suffering from NCDs. The purpose of this study is to describe the individual risk of suffering from NCDs based on the CERDIK behavior. This qualitative study used a cross-sectional design. A sample of 238 individuals who visited fast food restaurants in Blitar were selected by simple random sampling. Data collection used a CERDIK behavior questionnaire consisted of 20 knowledge questions, 29 attitude statements, and 20 practice statements. Data collection was conducted in July - August 2020. The risk of individuals suffering from NCDs in the low category was 8.4%, 81.1% moderate, and 10.5% high. Practice has an important role in individuals at risk of suffering from NCDs and most individuals are in the moderate category, while a small proportion are in the low and high risk category. It is hoped that health workers routinely and continuously campaign for CERDIK behavior as an effort to prevent NCDs.